The inhibition of vascular smooth muscle cell migration by peptide and antibody antagonists of the alphavbeta3 integrin complex is reversed by activated calcium/calmodulin- dependent protein kinase II. - Bilato, C (1997)
The migration of vascular smooth muscle cells (VSMCs) is thought to play a key role in the pathogenesis of many vascular diseases and is regulated by soluble growth factors/ chemoattractants as well as interactions with the extracellular matrix. We have studied the effects of antibodies to rat beta3 and human alphavbeta3 integrins on the migration of VSMCs. Both integrin antibodies as well as cyclic RGD peptides that bind to the vitronectin receptors alphavbeta3 and alphavbeta5 significantly inhibited PDGF-directed migration. This resulted in a reduction in the accumulation of inositol (1,4,5) trisphosphate and the activation of calcium/calmodulin-dependent protein kinase II (CamKII), an important regulatory event in VSMC migration identified previously. PDGF-directed VSMC migration in the presence of the anti-integrin antibodies and cyclic RGD peptides was restored when intracellular CamKII activity was elevated by either raising intracellular calcium levels with the ionophore, ionomycin, or infecting with a replication-defective recombinant adenovirus expressing a constitutively activated CamKII cDNA (AdCMV.CKIID3). Rescue of rat VSMCs was also observed in stably transfected cell lines expressing constitutively activated but not wild-type CamKII. These observations identify a key intermediate in the regulation of VSMC migration by outside-in signaling from the integrin alphavbeta3.